STRATEGI DAN METODE PENDIDIKAN KARAKTER - Surotul Yasin (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2017)
It is appropriate that the implementation of education in the school and madrasah aims to develop all potential learners in both the cognitive, psychomotor and affective domains. Cognitive is the intelligence of thinking, is expected to follow the existing programs in educational institutions learners have the ability to think better. Psychomotor is a skill development field, it is through this education that learners are expected to have skills in a particular field. Affective is the development of the attitude of learners in a better direction. With learners are in the educational environment is certainly expected to have a superior attitude and behavior. The development of the affective sphere that the current era we often hear with the term education of character, is still very interesting to continue reviewed. In relation to finding the right strategies and methods to be implemented both at school and madrasah. Strategy and method is very important in the implementation of education. If possible, say these strategies and methods is the key to the effective implementation of education. This paper offers alternative strategies and methods that can be used in the organization of character education. With the strategies and methods offered this character education is expected in the school environment maupu madrasah can be well organized and able to print a generation of character.